IEEE ACCESS SPECIAL SECTION EDITORIAL: REAL-TIME MACHINE LEARNING APPLICATIONS IN MOBILE ROBOTICS - Ucar, Aysegul; Grizzle, Jessy W.; Ghaffari, Maani; Wahde, Mattias; Akin, H. Levent; Baltes, Jacky; Miro, Jaime Valls (Ieee-Inst Electrical Electronics Engineers Inc, 2021)
[Abstract Not Available]